Mergers in perspective - Brozen, Yale (Washington : American Enterprise Institute for Public Policy Research, 1982)
The publication analyses mergers of corporations in the United States in the 20th century. Topics covered include: perspectives on mergers; conglomerate mergers and efficiency; mergers versus entry de Novo; aggregate concentration, economic and political power of the 200 dominant firms.
Includes bibliographical references.
lje 10/04/17
Loans
Keywords: Industrial concentration; Consolidation and merger of corporations